Global competition, institutional context, and regional production networks: Up- and downgrading experiences in Romania's apparel industry - Leonhard Plank; Cornelia Staritz (Austrian Foundation for Development Research (ÖFSE), 2014)
Regional suppliers still play an important role in the global apparel industry. By studying the experience of Romania's apparel sector, the paper highlights, first, the importance of multiscalar institutional, macro and policy contexts in analyzing the articulation of and up- and downgrading experiences in global production networks. These include the Multi-Fibre Arrangement, EU trade agreements and accession, the global economic crisis, and the specific institutional and policy context of post-Socialism. Second, the paper stresses the existence of diverse, non-linear and uneven up- and downgrading trajectories and of reactive adaptation rather than pro-active firm strategies. This questions the ideal upgrading account often portrayed in chain and network research.
Keywords: 330; Romania; apparel; global production networks; trade policy; upgrading; downgrading